Determinants of Electric Motorcycle Purchase Intention in Surabaya: An Analysis of Environmental Awareness, Green Price, Attitude, and Financial Well-being - Maqbula Arochman; Titik Inayati; Surenggono Surenggono (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Environmental issues such as soil pollution, forest fires, and increasing air pollution have become significant concerns for both the government and the public. Rising awareness of environmental preservation encourages society and industry to seek sustainable solutions, including the use of eco-friendly vehicles. This study aims to analyze the influence of environmental awareness, green price, attitude, and financial well-being on the purchase intention of electric motorcycles in Surabaya. The research employs a quantitative approach with data collected via Google Form questionnaires. The population consists of Surabaya residents interested in purchasing electric motorcycles in the future. The sampling technique used is non-probability sampling with a purposive sampling method, resulting in 138 respondents. Data analysis was conducted using multiple regression. The results indicate that environmental awareness, attitude, and financial well-being significantly influence purchase intention, while green price does not have a significant effect. The coefficient of determination (R² = 0.843) indicates that the model is capable of explaining 84.3% of the variance in purchase intention, which can be classified as very strong. The multicollinearity test results show that all variables have tolerance values greater than 0.10 and VIF values below 10, indicating that no multicollinearity issues are present in the model. These findings emphasize the importance of psychological and economic factors in shaping the intention to buy eco-friendly vehicles. This research contributes to the literature on green consumer behavior by integrating the dimension of financial well-being into the purchase intention model and serves as a reference for the government in formulating policies related to the development of electric vehicles.